Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Kloosterman sum is defined as

$$K(a,b;m)=\sum_{0\leq x \leq m-1}_{\gcd(x,m)=1} e^{2\pi \mathcal{i} (ax+bx^*)/m}$$

where $a,b,m \in \mathbb{N}$ and $x^*$ is the inverse of $x$ modulo $m$. Now there is a simple property of Kloosterman sum, which is that $K(1,mn;q)=K(m,n;q)$ with $\gcd(m,q)=1$, but how to show it is true? How should the $\gcd(m,q)=1$ condition be used in the proof?

share|cite|improve this question

1 Answer 1

up vote 4 down vote accepted

Write down the formula for $K(1,mn;q)$ and note the effect of the change of variable which replaces $x$ with $mx$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.